Destructive and nondestructive characteristics of solidified reservoir sediments incorporating microstructural analyses - Jamsawang, Pitthaya; Poorahong, Hatairat; Jongpradist, Pornkasem; Likitlersuang, Suched; Chaiyaput, Salisa (My University, 2022)
Reservoir sediments create a range of severe problems for hydropower dams. Although reservoir sediments can be excavated, nonetheless, sizeable dumping lands for such excavated sediments are unavailable at this time. This paper presents an experimental investigation of the destructive and nondestructive properties and microstructural characteristics of reservoir sediments solidified with fly ash–cement blend for reuse as construction materials. The obtained natural sediment was classified as well-graded sand with silt. The destructive experiments comprised unconfined compression, indirect tension, California bearing ratio, resilient modulus, and durability against wet–dry cycle tests, while the nondestructive experiments included a free–free resonance test. Microstructural investigations consisting of X-ray diffraction, thermogravimetric analysis, scanning electron microscopy, and energy-dispersive X-ray spectrometry were performed to verify the macroscale test results. The results showed that fly ash–cement blend exhibited increased strength values on the order of 2 to 9 times that of unsolidified sediments. Using fly ash-blended cement was more effective than using sole cement or sole fly ash, and mixtures with 10% fly ash delivered the best strength and modulus values. Various functional empirical correlations were proposed. Utilizing six wet–dry cycles is acceptable because the strength of the samples subjected to the six wet–dry cycles was lower than the given value. The results of the peak intensities of calcium silicate hydrate, mass losses, calcium contents, and scanning electron microscopy images derived from the microstructural investigations confirmed the macroscale test results.
Keywords: Destructive test; Durability; Fly ash-blended cement; Microstructure; Nondestructive test; Reservoir sediment